2015
DOI: 10.1007/s13197-015-2127-2
|View full text |Cite
|
Sign up to set email alerts
|

Influence of pre-drying treatments on physicochemical and organoleptic properties of explosion puff dried jackfruit chips

Abstract: The effects of hot air drying (AD), freeze drying (FD), infrared drying (IR), microwave drying (MV), vacuum drying (VD) as pre-drying treatments for explosion puff drying (EPD) on qualities of jackfruit chips were studied. The lowest total color differences (ΔE) were found in the FD-, MV-and VD-EPD dried chips. Volume expansion effect (9.2 %) was only observed in the FD-EPD dried chips, which corresponded to its well expanded honeycomb microstructures and high rehydration rate. Compared with AD-, IR-, MV-and V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 32 publications
4
28
0
1
Order By: Relevance
“…Organoleptic evaluation of food, or drugs, is that which stimulates the sense organs taste, colour, odor, and feel. Organoleptic tests is a very important quality control tool in food industry (Yi et al, 2015). In present work, the crosslinked films were used as wrapping film on chocolate and Indian vegetable puff.…”
Section: Organoleptic Testmentioning
confidence: 99%
“…Organoleptic evaluation of food, or drugs, is that which stimulates the sense organs taste, colour, odor, and feel. Organoleptic tests is a very important quality control tool in food industry (Yi et al, 2015). In present work, the crosslinked films were used as wrapping film on chocolate and Indian vegetable puff.…”
Section: Organoleptic Testmentioning
confidence: 99%
“…Accordingly, the samples with wide range of pore size distribution also exhibited a wide range of wall thickness distribution. The walls in the carrot chips demonstrated functional architecture in porous fruit or vegetable chips, and their thickness and rigidity are considered to be greatly responsible for the hardness and crispness of crispy products . Specific to the carrot chips, the thinner and concentrated walls induced the lower hardness of the un‐osmotic carrot sample (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…The walls in the carrot chips demonstrated functional architecture in porous fruit or vegetable chips, and their thickness and rigidity are considered to be greatly responsible for the hardness and crispness of crispy products. 33 Specific to the carrot chips, the thinner and concentrated walls induced the lower hardness of the un-osmotic carrot sample (Table 1). Combined with the microstructural analysis, it is further indicated that the textural and structural qualities of the carrot chips pretreated with apple juice concentrate were equal to the sucrose and maltitol pretreated chips.…”
Section: Wileyonlinelibrarycom/jsfamentioning
confidence: 98%
“…All prepared samples (I-VII) were evaluated for color, odor and taste as per the recent protocol 13,14,15 .…”
Section: Determination Of Organoleptic Featuresmentioning
confidence: 99%